Pelatihan Pengamatan Burung pada Pemuda Kampung Tabrik Desa Gekbrong Kabupaten Cianjur Dalam Mendukung Program Eduekowisata - Agus Pambudi Dharma; Meitiyani (Jurnal Pengabdian Masyarakat Formosa, 2022)
Birdwatching is a tourism that is still rare in Indonesia and has great potential to be developed. This training aims to tecah bird theory and bird watching as well as to become a special interest tour guide for birdwatching, which in the future the youth will earn additional income from guiding tourist and researchers. The method used is with discussions and hands-on practice in the forest. During the training in the field, 6 species of birds were found, including the Erasian sparrow, peking bondol, cucak finches, kestel bird, brontok eagle, and javanese eagle.